Nieuwe voorgevels met vormen uit vervlogen tijden: Brussel en het stedenbouwkundig “Îlot Sacré”-plan uit 1960 - Dominik Scholz (Brussels Studies)
Following a decision by the municipal council, the City of Brussels’ appearance became resolutely historic once again as of 1960. Many private buildings in the historic centre were adorned with old-fashioned facades. This era was regarded as being destructive to the old part of the city, yet paradoxically, it led to a reinforcement of its historic character – a little known phenomenon until now. Is this an early expression of a criticism of progress which emerged elsewhere in Europe in the 1970s? This article looks at urban planning in Brussels from a new angle. Through an analysis of stakeholders and ideas, it examines the reasons behind the construction of a new historic centre from the 1950s to the 1970s. This article shows that these reasons do not lie in the local patriotism of municipal representatives, but in a complex synergy between official urban planning policy, the successful mobilisation of protest groups and a desire for socio-economic development.